THE QUALITY CONTROL OF INA-CBG’S CODING AS A CAUSE OF NEGATIVE CLAIM AT BAGAS WARAS KLATEN HOSPITAL - Veronica Retno Setyaningsih; Mahendro Prasetyo Kusumo; Arlina Dewi (Universitas Muhammadiyah Semarang, 2017)
The pattern of payment that is applied by Jaminan Kesehatan Nasional (JKN) in advanced health facilities (hospitals) is a prospective payment pattern. Prospective Payment pattern known as casemix is a grouping diagnoses and procedures with reference to clinical characteristics which is similar and resource used or maintenance cost is similar. The grouping is done by software groupers. Bagas Waras hospital in making diagnosis grouping sometimes experiences the negative difference (loss) between the real cost of hospital fees in accordance with the Indonesia Case Based Group (INA CBGs) cost package approved by Badan Penyelenggara Jaminan Sosial (BPJS).This study is to determine the cause of the change file BPJS claims that the negative consequences of coding problems after qualitycontrol of INA-CBGs coding in Bagas Waras hospital Klaten. This study was a qualitative research design action (Action Research). This study used a model of action research (Action Research) of S Kemmis and R McTaggart which is designed through two cycles of the procedure: (1) planning , (2) action (3) observation, (4) reflection in each cycle. The research instrument used a questionnaire. Analysis of the data used qualitative analysis and quantitative analysis.The results showed that the frequency of claims BPJS start of the cycle I, II and III, there was a decreasing in the proportion of the, it is due to an error coding, Leght OfStay (LOS) extends, the cost of medical action that is excessive, and Excess Cost investigations. In improving the ability of diagnosis coding, Bagas Waras hospitalcontinuously strives to improve their ability to apply the Hospital Information System (SIRS).The cause of negative claim in a file BPJS after INA-CBGs control coding in Bagas Waras hospital is the employees do not understand the overall coding system, and do not run the monitoring and evaluation system of coding. Keyword : Negative Claim of BPJS, Coding INA CBG's